Chinese as a second language teachers' cognition in teaching intercultural communicative competence. (November 2018) - Gong, Yang; Hu, Xiang; Lai, Chun
Abstract: The development of intercultural communicative competence has recently emerged as one of the major foci in language education. The rise of Chinese as an international language has increased demand for studies exploring how Chinese language teachers teach intercultural communicative competence. This study investigated: (1) Chinese language teachers' pedagogical cultural knowledge and objectives in teaching intercultural communicative competence; and (2) the contextual factors (i.e., overall university surroundings, computer accessibility, academic atmosphere, and colleagues and superiors) influencing their pedagogical cultural knowledge and objectives in teaching intercultural communicative competence. Based on a survey of 43 university teachers from China, it shows that the participants had different degrees of familiarity with pedagogical cultural knowledge and that contextual factors affected their pedagogical cultural knowledge development. Moreover, the participants' objectives in teaching intercultural communicative competence were more skill-than knowledge- and attitude-oriented, and had different relationships with different contextual factors. The findings inform the development of in-service and pre-service teacher education programmes to help Chinese language teachers become effective intercultural language teachers.